THE EFFECT OF DEFATTING, WASHING FREQUENCY, AND QUALITY CHANGES DURING THE STORAGE OF SURIMI FROM PATIN FISH(Pangasius hypophtalamus) - Arlina Hidayati; Septiana Sulistiawati (Jurnal Harpodon Borneo, 2025)
Patin fish is a type of freshwater fish with white flesh, no fibres and no small bones, making it easier to process. One potential form of diversification that can be developed is surimi. The fat in the flesh must be removed because any fat remaining in the flesh will reduce the gel strength and sensory properties of the surimi due to fat oxidation. The methods used to remove fat are defatting and washing the surimi. Surimi protein can undergo degradation during frozen storage. Cryoprotectants are food additives that prevent protein denaturation in surimi during frozen storage. The objective of this study was to determine the optimal process for producing surimi from patin fish, specifically the defatting process (NaHCO₃ concentration), washing frequency, and quality deterioration during storage. The optimal NaHCO₃ concentration was 0.5%, which resulted in the highest fat reduction and the lowest protein reduction. The optimal washing frequency was once, which had the highest impact on the bite test and fold test values. The lowest quality deterioration of surimi during storage was observed in the treatment with cryoprotectant addition, which affected the soluble protein content, pH, moisture content, bite test, and fold test.